Calcium and Phosphor Retention in The Panhisterectomized Rats Fed High Calcium - Hartiningsih Hartiningsih (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
The objectives of the research was to study the effect of panhisterectomy on calcium (Ca) and phosphor (P) retention in the female Sprague Dawley rats that were fed teri which ratio of Ca:P is 3:1 for 12 weeks. Ten female of Sprague Dawley rats, 6 weeks of age were randomly divided into two groups (control and anhisterectomized groups) of five each. At 8 weeks of age, the rats of panhisterectomized group were panhisterectomized. At 20 weeks of age, they were placed into individual metabolic cages for balance study. The remaining of feed was collected for calcium and phosphor analyses. Every morning, from days 4 to 8 of the balance study, urine andfecal samples were also collected at the same time. The research results showed that calcium and phosphor retentions were significantly reduced (P<0.05) in panhisterectomized group compared to that of the control group. Fecal calcium excretion was a significantly higher (P<0.05), whereas fecal and urinary phosphor excretions were significantly higher (P<0.05) in the panhisterectomized group compared to that of the control group. It is concluded that panhisterectomy leads to a reduction of the calcium and phosphor retention in the Sprague Dawley rats that were fed high calcium.Keywords : panhisterectomized, calcium, phosphor retention, individual metbolic cages, Sprague Dawleyrats